MAN AND SUSTAINABLE LOW INCOME HOUSING - Emilia van Egmond; Stephen Agyefi Mensah (Journal of Architecture&ENVIRONMENT, 2011)
The importance of concern for the human dimension in sustainable design and engineering solutions for housing is the issue discussed in paper. It is based on literature studies. Sustainable housing encompasses the provision of residential buildings in a simultaneous pursuit to well-balance three dimensions: (1) economic dimension; (2) ecological dimension; (3) social or human dimension. This implies the promotion of capabilities by which individuals can fulfill their needs in ways that best suit them; consistent with their socio-cultural values and affordability whilst not exhausting the natural environment. The housing backlog and the need for adequate housing especially for low income households is still high in many countries. To cope with housing problems, Low Income Housing projects were carried out throughout the world. The literature studies showed that the majority of research on functionality and adaptability of the houses to meet the requirements of individual households has taken place in advanced countries. Most studies tended to focus on technological issues being divorced from user demands, lifestyle and domestic activities. Further research onto the human dimension in design and engineering solutions for sustainable low income housing in DCs is evident.